2005
DOI: 10.1158/1078-0432.ccr-05-1142
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Lymphangiogenesis in Inflammatory Breast Carcinoma: A Histomorphometric Study

Abstract: Purpose: At the time of diagnosis, metastatic dissemination of tumor cells via the lymphatic system has occurred in nearly all patients with inflammatory breast cancer (IBC). The objective of this study was twofold: (a) to determine which is the most suitable marker of lymph vessels in primary breast tumors and (b) to compare histomorphometric lymph vessel variables in IBC and non-IBC. Experimental Design: Serial sections of 10 IBCs and 10 non-IBCs were immunostained for D2-40, LYVE-1, podoplanin, and PROX-1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
3
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(136 citation statements)
references
References 27 publications
6
120
3
7
Order By: Relevance
“…41,44 Others, however, maintain that the tumor invades new lymphatics that are formed during lymphangiogenesis within the tumor mass or at the invasive front of the tumor. 37,39 In this study, most foci of D2-40 þ lymph vessel invasion occurred at the invasive front of the tumor, indicating that metastasis could occur via pre-existing lymphatics or via newly formed lymphatics at the invasive front of the tumor.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…41,44 Others, however, maintain that the tumor invades new lymphatics that are formed during lymphangiogenesis within the tumor mass or at the invasive front of the tumor. 37,39 In this study, most foci of D2-40 þ lymph vessel invasion occurred at the invasive front of the tumor, indicating that metastasis could occur via pre-existing lymphatics or via newly formed lymphatics at the invasive front of the tumor.…”
Section: Discussionmentioning
confidence: 59%
“…36 Furthermore D2-40 has been shown to be the best marker for lymphatic endothelium. 37 In this study, we identified lymph vessel invasion using D2-40 in 82/303 (27%) of cases of node negative breast cancer. We showed D2-40 þ lymph vessel invasion significantly correlated with H&E þ (P ¼ o0.0001).…”
Section: Discussionmentioning
confidence: 95%
“…Opposing results have been reported by later studies where functional intratumoural lymphatics were detected in xenografted tumours [11]. With human breast cancer certain studies have reported an absence of both intratumoural lymphatics and of lymphangiogenesis [12][13][14] whereas others have detected lymphatics both inside and around the tumour [15][16][17]. The importance of the lymph vessel density (LVD) in promoting metastatic spread of breast cancer is questionable [18,19] and which vessels, newly formed lymphatics or pre-existing ones, play the more important role in the initial dissemination of tumour cells is uncertain.…”
Section: Introduction and Aimsmentioning
confidence: 73%
“…In the current study, intratumoural lymphatics referred to vessels within the inner 2/3 core of the tumour including vessels both among the tumour cells and/or in the tumour stroma. Other studies refer to intratumoural lymphatics as any vessels within the tumour area, either in the peripheral part or in the inner core [15]. Intratumoural lymphatics have also been referred to as vessels present only among tumour cells, while those present within the tumour stroma were separately counted and analyzed [39].…”
Section: Discussionmentioning
confidence: 99%
“…83,84 Variable results on intratumoral vessels may be due to different staining methods, tumor types or due to inconsistency in their definition, such as whether lymphatic vessel within stromal structures inside the tumor mass is regarded as intratumoral. 85 When vessels in intratumoral stromal structures were considered intratumoral, they were observed in 80% of breast cancer cases, 86 whereas when vessels in stromal structures were not included, intratumoral vessels were observed in only 10% of ductal breast carcinomas. 87 Invasively growing tumors could co-opt pre-existing lymphatic vessels, whereas expansive growth could recruit lymphangiogenesis.…”
Section: The Role Of Vegfs In Lymphangiogenesismentioning
confidence: 99%